Ruthenium‐Catalyzed ortho‐Alkenylation of Aroylgermanes. Issue 19 (2nd April 2020) - Wang, Hai; Yuan, Yang; Zhang, Youcan; Franke, Robert; Wu, Xiao‐Feng
Abstract : In this communication, a ruthenium‐catalyzed ortho ‐alkenylation of acylgermanes with electron‐deficient alkenes through direct C–H bond activation has been developed. With acylgermane as the directing group, this method provides a straightforward access to diverse acylgermanes derivatives with good functional group tolerance and site‐selectivity under mild reaction conditions. Abstract : A ruthenium‐catalyzed ortho ‐alkenylation of acylgermanes with electron‐deficient alkenes through direct C–H bond activation has been developed. With acylgermane as the directing group, this method provides a straightforward access to diverse acylgermanes derivatives with good functional group tolerance and site‐selectivity under mild reaction conditions.